Research Brief #6: Aflatoxin. - Shively, Gerald.; Sununtnasuk, Celeste.; Jing, Hao. (Tufts University. Tisch Library., 2016)
This brief explains the sources of aflatoxin, its importance in nutrition-related research, and its effects on humans, animals, and economics.; Keywords: CRSP, Nutrition, Research Brief, Agriculture, Nepal, Uganda, Aflatoxin.